SEBASTIAN RODRIGUES’ CHARACTER CHANGES DUE TO JAPANESE SOCIAL POWER IN THE SILENCE MOVIE - Maria Gratia da Silva; Priyatno Ardi (Sanata Dharma University, 2019)
The present study investigates the changes of the characteristics of Sebastian Rodrigues, a Catholic priest, before and after experiencing the social power in Japan. It also investigates the influences of the Japanese social power on the changes of Sebastian Rodrigues’ characteristics in the Silence movie. The setting of the movie is the seventeenth century in Japan, on which Christianity was banned. Sociocultural-historical approach was employed to analyze the movie. The results of the analysis shows that Sebastian Rodrigues’ characteristics before he experiences Japanese social power include being compassionate, faithful, optimistic, and unconfident. After he experiences the social power, his characteristics change into helpless, despair, oppressed and senseless. The Japanese social power influences Rodrigues’ characteristics in five ways, namely forcing him to find the unfairness and violence, catching him, mocking him, making him witness the murder, and forcing him to apostatize. Hence, the power changes Rodrigues’ characteristics.